THE QUALITY OF QUAIL EGGS GIVEN RATION WITH THE ADDITION OF CHICKEN EGG SHELL FLOUR - R. M., Ginting; Wirapartha, M.; Wijana, I W. (Jurnal Peternakan Tropika; Vol 11 No 3 (2023): Vol. 11 No. 3 Tahun 2023; September - December, 2023)
Quails (Coturnix-coturnix japonica) are the result of domestication, which were originally wild in nature and later became breedable livestock. Research has been conducted to determine the effect of adding chicken eggshell flour on the ration on the quality of Japanese quail eggs which has been carried out for 4 weeks at Jalan Prasman Unud Blok F-30 housing Bukit Jimbaran and the Poultry Livestock Laboratory, Faculty of Animal Husbandry, Udayana University.  The research design used was a Complete Randomized Design (RAL) for each test taken by 4 quails. The four treatments given were P0: rations without chicken eggshell flour, P1, P2, and P3 rations with the addition of 4%, 6%, and 8% purebred chicken eggshell flour, respectively. The variables observed were egg weight, eggshell weight, eggshell thickness, egg white weight, yolk weight, yolk color, HU (Haugh Unit), and egg pH.  The data results were analyzed using fingerprint anallition, if there were noticeable differences in the treatment followed by duncan's Multiple Distance Test. The results showed that the feeding of eggshell flour by 6% and 8% increased markedly (P<0.05) to egg weight, and yolk weight, while 4%-8% had not been able to increase eggshell weight, egg white weight, egg yolk color, HU (Haugh Unit), and egg pH statistically did not differ markedly (P>0.05). The conclusion of this study is that giving 6% and 8% eggshell flour can improve the quality of quail eggs aged 10 weeks.   Keywords : quail, egg quality, chicken egg shell flour